Morphology and vase life of cut torch ginger (Etlingera elatior) inflorescences - Gratuito, Maria Belinda B. (2008)
Torch ginger (Etlingera elatior) is a tropical plant belonging to Zingiberaceae family. This attractive plant attracts many growers for economic and ornamental purposes. However, there is limited study on its inflorescence. This study aimed to characterize the different maturity stages of the torch ginger inflorescence and determine the vase life as well as some postharvest characteristics as influenced by maturity, sucrose, and 1-methylcyclopropene. The various inflorescence stages tagged as 25, 50, 75 and 100% each exhibited distinct morphological characteristics. In situ the average number of days to reach the fully opened stage was 36. The number of involucral bracts, appearance of the true florets, inflorescence and cone (floral bracts) size varied in all the stages. Vase file of 75% opened inflorescences ranged from 4.2 to 9 days. Vase life was shortest at 25 and 100% opened stages. Pulsing the sucrose (10, 20, 30, and 40%) for 12 or 24 hours. Did not positively influence vase life and water uptake but improved floret opening and cone (floral bracts) size. 1-methylcyclopropene hastened the appearance of the true florets, but did not prolong vase life. Increasing involucral and floral bract browning and wilting, senescence of true florets, and reduced visual quality indicated the termination of vase life.